Case Study On Kumpulan Perangsang Selangor Sdn Bhd -Water Utility Business In Selangor - Zainal Abidin, Khairul Nidzham (2009)
This report presents author in-depth study on Kumpulan Perangsang Selangor Sdn Bhd based on the analysis using the matrixes and model learned.